Paradigm Change? Cardiac Output Better Associates with Cerebral Perfusion than Blood Pressure in Ischemic Stroke - Fuhrer, Hannah; Reinhard, Matthias; Niesen, Wolf-Dirk (Frontiers in Neurology, 2017)
Introduction: In patients with acute ischemic stroke penumbral perfusion is maintained by collateral flow and so far is maintained by normal mean arterial pressure (MAP) levels. Since MAP is dependent on cardiac function, optimization of cardiac output might be a valuable hemodynamic goal in order to optimize cerebral perfusion. Methods: Cerebral perfusion was assessed by transcranial colour-coded duplex and transcranial perfusion sonography in 10 patients with acute large hemispheric stroke. Time to peak- values (TTP) of defined regions of interests (ROI) within the middle cerebral artery territory were assessed bilaterally in addition to mean flow velocities (MCAv) of the middle cerebral artery (MCA). Via semi-invasive advanced hemodynamic monitoring systemic hemodynamic parameters were assessed, including MAP and cardiac index (CI). Patients received sonographic follow-up after optimizing CI. Results: TTP values of the deeply located ROIs of the non-affected as well as the affected hemisphere correlated highly significantly with CI (in affected side r= -0.827, p=0.002; and in non-affected side r= -0.908, p< 0.0001). This demonstrates dependence of cerebral perfusion on CI, whilst correlation with MAP was not detected. Neither CI nor MAP revealed significant correlation with MCAv.